Finite element modelling of reinforced concrete beam using COSMOS/M; Experimental study on timber space truss; Stress-strain relationship for light red meranti glued layered timber short columns; Engineering characteristics of quicklime treated slime from ex-mining road; Tindak balas alkali-silika dan kesannya ke atas rasuk-dalam konkrit bertetulang; Analisis tegasan menggunakan kaedah unsur sempadan bagi rasuk kayu / [mikrofilem] - Ahmad Ruslan Mohd. Ridzuan; Ahmad Shahrir Ismail; Chang, Chee Wei; Md. Khairi Mohd. Amin; Su, Biing Yueh; Suhaimi Abu Bakar @ Md Ramli (Sekudai : UTM, 1994)
Thesis (Master of Civil Engineering (Structures)) - Universiti Teknologi Malaysia, 1994